Thoughts Behind Action: Recidivism among Children-in-Conflict with the Law - Andrie Jann Akilith (Research Synergy Foundation Press, 2023)
This study examined the recidivism of Children-in-Conflict with the Law (CICL) using three (3) theories, the Ecological Systems Theory, Labeling Theory, and Differential Association Theory. Utilizing Interpretative Phenomenological Analysis (IPA), children ages 15 years and 1 day but not more than 18 years old with pending cases at law who had previously committed offenses at the Barangay or Prosecutor level in Second Chance Home of Calamba (SCH) were asked utilizing a semi-structured interview. To understand how the theories influenced the persistence of recidivism among CICL, the researcher examined their physical, social, and cultural backgrounds. This study generated eleven (11) superordinate themes which were: Dysfunctional Households; Multifaceted Issues in Early School Leaving; Inconsistent Community Support; Offender Profiling; Perceived Psychological Distress due to Formal Labels; Social Marginalization; Inexistent CICL Segregation; Social Modeling; and Delinquent Peers and Family.This study aimed to inform policies and practices that may aid in lowering or stopping CICL recidivism by studying how these theories manifest in participants' actual experiences. By identifying the risk factors associated with recidivism, researchers and policymakers may develop personalized prevention programs that address the core causes of delinquency and aid at-risk adolescents. Investigating recidivism among CICL can result in safer communities and better outcomes for young people involved in the criminal system. This study also proposed an enhanced diversion program for CICL who are currently receiving rehabilitation, CICL who are released as minors, and CICL who are released as adults.